Leptin receptor Q223R polymorphism in Egyptian female patients with breast cancer - Mona Abo-Bakr El-Hussiny; Mohmed Ali Atwa; Waleed Elnahas Rashad; Dalia A. Shaheen; Nora Marzouk Elkady (Contemporary Oncology)
Aim of the study: Breast cancer is the most common cause of death in women. Obesity has been associated with increased risk of breast cancer in post-menopausal women. It induces chronic inflammation, which increases local and systemic levels of cytokines and adipokines such as leptin. Leptin (LEP) and leptin receptor (LEPR) genes have several polymorphisms in humans. This study aims to assess the association between blood levels of leptin and LEPR Q223R gene polymorphism in patients of cancer breast. Material and methods : The current study was carried on 48 female breast cancer patients and 48 heathy female subjects. Carcinoembryonic antigen (CEA), cancer antibody CA15-3, and leptin hormone were determined. Single nucleotide polymorphism of LEPR Q223R was assessed by PCR/RFLP. Statistical analysis used: The statistical analysis of data was done by using SPSS version 20. Results : There were significant increases in the concentrations of CEA (p = 0.004), CA15-3 (p < 0.001), and leptin hormone (p < 0.001) in BC patients in relation to the respective concentrations in control subjects. CEA and CA 15-3 showed significant differences between various BC stages. As regard to LEPR Q223R gene polymorphism, AA genotype showed significantly higher frequency in BC patients when compared to their respective controls, with higher risk to develop BC. Conclusions : Leptin hormone shows significantly higher concentrations in BC patients. As regard to LEPR Q223R gene polymorphism, AA genotype showed significantly higher frequency in BC patients.